Analisis Keikutsertaan Skrining HIV Pada Ibu Hamil - Sri Hernawati Sirait (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2023)
HIV/AIDS in various parts of the world, including in Indonesia is currently considered the most contagious disease among any diseases, until now HIV/AIDS is still unresolved and continues to be a problem in the world. HIV can be infected vertically from HIV positive mothers who are detected through HIV testing for babies during pregnancy, childbirth and breastfeeding which is currently under the world's attention because it affects the quality of human resources. The aim of the study was to analyze the predisposing, enabling and motivating factors of pregnant women to screen for HIV. This study used a quantitative approach with a survey research type with a cross-sectional design. The population and sample of the study were all pregnant women in the Tapian Dolok Public Health Center, Simalungun Regency, who met the inclusion and exclusion criteria, as many as 51 pregnant women. The sampling technique was carried out using non-probability sampling, namely by means of consecutive sampling. How to collect data by using a questionnaire. Bivariate data analysis used the chi-square test with a significance level of p<0.05 and multivariate data analysis used multiple logistic regression tests. The results showed that predisposing factors, namely education, sources of information, knowledge, counseling and voluntary HIV testing, had a significant relationship with participation in HIV screening in pregnant women, as well as supporting factors, namely husband's support with a value of p = 0.000. The prediction of the probability of pregnant women carrying out HIV screening is 86%, if pregnant women carry out HIV counseling and screening and receive information from health workers. Suggestion: It is necessary for health workers to provide clear, simple information and provide facilities for pregnant women to increase the scope of HIV screening.